Artificial Intelligence As a Teaching Partner: The Role of Chatbots in Indonesian Language Learning - Muh. Safar (PT. Anagata Sembagi Education, 2025)
This study examines the role of artificial intelligence (AI)-based chatbots as teacher partners in Indonesian language learning at the primary school level. Using a systematic literature review approach, this research synthesizes empirical evidence from reputable academic sources published between 2015 and 2024. The findings demonstrate that chatbots significantly enhance students’ literacy skills, including reading comprehension, sentence construction, vocabulary development, and speaking fluency through adaptive interaction and instant feedback. Moreover, chatbots support teachers by enabling differentiated instruction, efficient task management, and personalized learning pathways. However, successful implementation requires strong digital infrastructure, teacher digital competence, culturally relevant language design aligned with national standards, and ethical oversight. This study contributes novelty by emphasizing human-AI pedagogical collaboration in Indonesian primary classrooms, positioning chatbots as complementary learning partners rather than instructional replacements. The results underscore the necessity of capacity-building programs for teachers, strategic policy development, and collaborative AI development to foster ethical and culturally grounded AI-assisted language learning.